Transformations in anti-discrimination law - Anón, María José (Revus (Ljubljana), 2020)
This article proffers a reflection on some of the most recent feminist legal proposals within the context of anti-discrimination law. The notion of structural discrimination is an appropriate starting point for exploring two relevant aspects of anti-discrimination arguments: the review of comparative type rationale and the weight given to the relevant comparator, and second, the meaning or purpose of the identification of gender stereotypes. As a further step in this field, the article provides an analysis that reinforces the proposal to advance anti-subordination law.
Keywords: antidiscrimination law; gender stereotypes; harm; podrejevalna diskriminacija; protidiskriminacijsko pravo; relevant comparator; relevantni kriterij primerjave; sistemska diskriminacija; spolni stereotipi; subordiscrimination; systemic discrimination; škoda